Motivational climate, interest, effort and learning progression in Chilean adolescents in relation to gender and physical activity - Carrasco-Venturelli, Hanrriette; Cachón-Zagalaz, Javier; Ubago-Jiménez , José Luis; Lara-Sánchez, Amador J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to examine whether a relationship exists between the motivational climate and adolescents' interest, effort, and progression in learning in Physical Education classes, considering both gender and physical activity level. The following questionnaires were applied: PMCSQ-2, IEPA, AYES, and PAQ-C to a sample of n=3169 Chilean adolescents. The results were studied through descriptive and correlational analyses showing that there are statistically significant correlations when students perceive that the teacher acts intentionally in their classes towards the task climate, they show greater interest, effort and progression in their learning, highlighting greater motivation in the group that has mild PA in both males and females. But when these variables are related to ego climate, they only correlate positively in men, and negatively in women. When the dispositional and contextual variables are correlated, there is greater interest, effort and progress in learning in the PE class in men. It is necessary for PE teachers to focus their classes on the homework climate, because this will promote greater interest, effort and progression in learning, and will encourage possible adherence to the acquisition of healthier lifestyles.